(untitled) (Research, Society and Development, 2021)
Urinary Tract Infections (UTI) affecting patients at Intensive Care Units (ICU) is a preoccupant reality, further aggravated by inadequate antimicrobial use and the alarming antimicrobial resistance in microorganisms. We evaluated the level of assertiveness regarding the use of antimicrobials during the empirical antibiotic-therapy (EA), in patients with UTI, comparing the empiric pharmacological treatments (EA) and those ones performed after the antibiogram (guided therapy). Moreover, we estimated the prevalence of the causative agents and analyzed the risk factors associated. This is an observational and cross-sectional study, undertaken in 2015, in which patients (both gender and all ages) with UTI and underwent antimicrobial therapy, enrolled at an ICU in a hospital in the southern region of the Brazilian state of Minas Gerais, Brazil, were evaluated. Among the 49 patients evaluated (28 females [F] and 21 males [M]), the mean age was 55±19 years (CI(95) 49-61) and the predominant age range was ≥70 years. Fourteen different microorganisms were identified. 28.3% (CI(95%) 16.2-40.4) of the UTI had Escherichia coli as causative agent (33.3% M and 28.6% F); 18.9% (CI(95%) 8.3-29.4) Acinetobacter baumannii (33.3% M and 10.7% F); 15.1% (CI(95%) 5.5-24.7) Klebsiella pneumoniae (19% M and 14.3% F); 11.3% Pseudomonas aeruginosa (9.5% M and 14.3% F); 5.7% Enterobacter aerogenes (14.3% M); 3.8% Klebsiella oxytoca; 3.8% Staphylococcus aureus (7.1% F); and 2% for each of the microorganisms as follows: Enterococcus faecalis (4.8% M); Proteus mirabilis (3.6% F); Enterobacter cloacae (3.6% F); Providencia rettgeri (4.8% M); Citrobacter koseri (3.6% F); Citrobacter freundii (3.6% F); and Yeasts (4.8% M). The prevalence of UTI caused by A. baumannii and P. aeruginosa in the ITUs were influenced by the patients’ sex (χ² with p<0.001). In the male sex, it there was “substantial” positive correlations between the most increased ages (in years) and the prevalence of UTI caused by E. coli (r = 0.69) or between the decreased ages and the prevalence of UTI caused by A. baumannii (r = -0.7). In the female sex, it there was an “extremely” positive correlation between the most increased ages and the prevalence of UTI caused by E. coli (r = 0.94; CI(95) 0.66-0.99; p<0.0014). The most used antimicrobials in an empirical fashion (EA) were: Ciprofloxacin (14.3% CI(95%) 4.7-24.1), Cefepime (14.3%), and Vancomicin (10%); and after antibiogram (guided therapy): Ceftazidime (16.3% CI(95%) 6-26.7), Ciprofloxacin (14.3% CI(95%) 4.5-24.1), Polymyxin B (10.2%), Imipenem (10.2%), and Ampicillin/sulbactam (8.2%). In 20% of cases, the EAs were considered “inappropriate/not correct”. However, we must also be aware of the clinical need and the immediacy for the treatment of UTIs in an ICU, since the disease can be fatal if a therapy is not instituted, therefore, we advise more detailed assessments, both of the rationality of use antibiotics, as well as the risk factors for the development of UTIs in ICUs.